EXPLORING THE BARRIERS OF AND RECOMMENDATIONS FOR ONLINE TEACHING AND LEARNING IN UNDERGRADUATE MEDICAL EDUCATION: A DESCRIPTIVE PHENOMENOLOGICAL STUDY - Muhammad Junaid Khan; Ahsan Sethi (Journal of Ayub Medical College Abbottabad, 2023)
Background: The advancement in science and technology has forced educational institutions worldwide to shift to online teaching and learning (T&L), including medical colleges in Pakistan. This qualitative study explores the barriers and recommendations for online classes among undergraduate medical students in Khyber Pakhtunkhwa, Pakistan. Method: The study included students from six medical colleges who were actively engaged in online T&L with a descriptive phenomenological approach. Result: The study resulted in a multitude of barriers hampering the overall quality of effectiveness of online T&L, including internet connectivity issues, communication gaps, health concerns due to prolonged screen time, challenges in joint family settings, and limited time for self-study. The lack of interactivity in online classes was a significant concern, as students felt they had limited opportunities to engage with their peers and instructors. The recommendation mainly targeted the fair and transparent assessment, and feedback mechanism with continuous monitoring that potentiate student engagement, training and improving resources that can increase the effectiveness and readiness of online medical education well for the transition to distance learning. Conclusion: It is important to modify and adopt meticulous methodical approaches like fair and transparent assessment methods, robust feedback mechanisms, improved resources, rigorous supervision, and thorough faculty development programs that will counterbalance similar barriers for a more effective and inclusive online learning environment.